Project symphony: Composing a masterpiece in a science laboratory - Sunghee Lee; Jamie Gudyka; Marnie Skinner; Jasmin Ceja-Vega; Amani Rabadi; Christopher Poust; Caroline Scott; Micaela Panella; Elizabeth Andersen; Jessica Said (iScience)
In the spirit of collaborative science, Prof. Sunghee Lee (Chemistry Professor at Iona University in New York, USA) embarked on her academic career with a vision to bring an interdisciplinary approach to undergraduate education. At a Predominantly Undergraduate Institution (PUI) such as Iona, she saw a unique opportunity to weave together teaching and research, creating a rich tapestry of learning experiences for students.Her goal was simple yet ambitious: to use research as a bridge connecting classroom theory to real-world interdisciplinary scientific practice.In this Backstory, Sunghee and her students and recent graduates reflect on the development and experiences that shaped their journey through Project Symphony and the resulting skills they’ve learned. The symphony they’ve created together is a testament to the transformative power of collaborative undergraduate research – a melody of discovery that continues to evolve and inspire.